2017
DOI: 10.1055/s-0043-120766
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI Findings in Cerebral Aspergilloma

Abstract: ZUSAMMENFASSUNG Ziel Zerebrale Aspergillose betrifft meist immunsupprimiertePatienten und weist aufgrund der oftmals unspezifischen Klinik ein hohes Morbiditäts-und Mortalitätsrisiko auf. Eine frühe Diagnosestellung ermöglicht die effektivere Einleitung der Therapiemaßnahmen und die Verbesserung des Outcome.Material und Methoden Die CT-und MRT-Aufnahmen von neun Patienten aus zwei Zentren wurden ausgewertet. Die Diagnose der zerebralen Aspergillose wurde mittels Biopsie und histopathologischer Begutachtung ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…MRI-T2 images can present hypointense or hyperintense, as well as cystic lesions with hypodense periphery and hyperdense center. The typical pattern on MRI-T1 was isointense/hypointense imaging with peripheral rim of hyperintensity and internal heterogeneous contrast enhancement, this phenomenon has also been reported in previous literature 17 . A single-center retrospective study showed that cryptococcal infection may present a hypointense lesion on the T2 image with a peripheral hyperintense edema shadow.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…MRI-T2 images can present hypointense or hyperintense, as well as cystic lesions with hypodense periphery and hyperdense center. The typical pattern on MRI-T1 was isointense/hypointense imaging with peripheral rim of hyperintensity and internal heterogeneous contrast enhancement, this phenomenon has also been reported in previous literature 17 . A single-center retrospective study showed that cryptococcal infection may present a hypointense lesion on the T2 image with a peripheral hyperintense edema shadow.…”
Section: Discussionsupporting
confidence: 76%
“…Although imaging can help with the diagnosis to some extent, the manifestations can vary depending on the pathogen, the immune status of the body and the age of the lesions 2,16,17 . In our patients, even with the same MRI sequence, the fungal infections manifested to different extents.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Neuroimaging techniques, such as contrast CT scan or MRI are important diagnostic toolsforthe identification of brain abscesses that help to differentiate a fungal cerebral abscess from a bacterial abscess. A fungal cerebral abscess presents with a typical finding of a hypodense lesion with a contrast-enhancing ring in a CT scan or MRI scan [ 8 ]. Unlike bacterial abscesses, which are usually solitary lesions, fungal abscesses are more likely to be numerous.…”
Section: Discussionmentioning
confidence: 99%